VizieR Online Data Catalog: The Cluster System of the LMC (Kontizas+ 1990) - Kontizas, M.; Morgan, D. H.; Hatzidimitriou, D.; Kontizas, E. (1994)
A new catalogue of clusters in the Large Magellanic Cloud has been constructed from searches of the IIIa-J component of the ESO/SERC Southern Sky Atlas. The catalogue contains coordinate and diameter measurements of 1762 clusters in a 25x25{deg} area of sky centred on the LMC, but excluding the very crowded 3.5 square deg. region around the Bar. The distribution of these clusters appears as two superimposed elliptical systems. The higher density inner system extends over about 8d; the lower density outer system can be represented by 13d X 10d disc inclined at 42d to the line of sight. There are suggestions of two weak "arms" in the latter. (1 data file).
Keywords: Associations: stellar; Clusters: globular; Clusters: open; Magellanic Clouds